REDESIGN LAYOUT WORKSTATION PROSES INJECTION MOLDING BERDASARKAN WORKLOAD ANALYSIS DAN PROSES SIMULASI PADA PEMBUATAN KOMPONEN LCDTV - Mulyana, Fajar; Sugiono, Sugiono; Tama, Ishardita Pambudi (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2015)
Abstract Productivity improvement of the company can be reach with many effort, which are minimizing waste, improving the utility of operator, and also redesigning layout facilities. Based on the observation, idle time of operator for the injection process is 30 minutes. If the delay will be compare with the company losses, it is equal to IDR. 1.001.700/operator/month. Based on this problem, redesign of the facilities layout is a solution to improve utilities and workload of operator. The result of this research, alternative layout has design based on simulation and the analysis of Activity Relationship Chart (ARC). It could be minimized the material handling 49.4 meters and 42.9 seconds. For the financial analysis, it can be minimized the labour cost IDR 14.684.670/month and also the material handling cost at least IDR 54.262/month.